Hybrid online platform learning application - Mohamad Ayadi, Nurul Ainn (Universiti Teknologi MARA, Perak, 2022)
The Going Class is a platform that allows educators to create online classes whereby they can store the course materials online, managements, quizzes and exam, monitor due dates, grade result and provide text book online all in one place.